Controlled trial of budesonide–formoterol as needed for mild asthma - Beasley, R; Holliday, M; Reddel, H; Braithwaite, I; Ebmeier, S; Hancox, R; Harrison, T; Houghton, C; Oldfield, K; Papi, A; Pavord, I; Williams, M; et al. (Massachusetts Medical Society, 2019)
BACKGROUND In double-blind, placebo-controlled trials, budesonide–formoterol used on an as-needed basis resulted in a lower risk of severe exacerbation of asthma than as-needed use of a short-acting β2-agonist (SABA); the risk was similar to that of budesonide maintenance therapy plus as-needed SABA. The availability of data from clinical trials designed to better reflect clinical practice would be beneficial. METHODS We conducted a 52-week, randomized, open-label, parallel-group, controlled trial involving adults with mild asthma. Patients were randomly assigned to one of three treatment groups: albuterol (100 μg, two inhalations from a pressurized metered-dose inhaler as needed for asthma symptoms) (albuterol group); budesonide (200 μg, one inhalation through a Turbuhaler twice daily) plus as-needed albuterol (budesonide maintenance group); or budesonide–formoterol (200 μg of budesonide and 6 μg of formoterol, one inhalation through a Turbuhaler as needed) (budesonide–formoterol group). Electronic monitoring of inhalers was used to measure medication use. The primary outcome was the annualized rate of asthma exacerbations. RESULTS The analysis included 668 of 675 patients who underwent randomization. The annualized exacerbation rate in the budesonide–formoterol group was lower than that in the albuterol group (absolute rate, 0.195 vs. 0.400; relative rate, 0.49; 95% confidence interval [CI], 0.33 to 0.72; P<0.001) and did not differ significantly from the rate in the budesonide maintenance group (absolute rate, 0.195 in the budesonide–formoterol group vs. 0.175 in the budesonide maintenance group; relative rate, 1.12; 95% CI, 0.70 to 1.79; P=0.65). The number of severe exacerbations was lower in the budesonide–formoterol group than in both the albuterol group (9 vs. 23; relative risk, 0.40; 95% CI, 0.18 to 0.86) and the budesonide maintenance group (9 vs. 21; relative risk, 0.44; 95% CI, 0.20 to 0.96). The mean (±SD) dose of inhaled budesonide was 107±109 μg per day in the budesonide–formoterol group and 222±113 μg per day in the budesonide maintenance group. The incidence and type of adverse events reported were consistent with those in previous trials and with reports in clinical use. CONCLUSIONS In an open-label trial involving adults with mild asthma, budesonide–formoterol used as needed was superior to albuterol used as needed for the prevention of asthma exacerbations. (Funded by AstraZeneca and the Health Research Council of New Zealand; Novel START Australian New Zealand Clinical Trials Registry number, ACTRN12615000999538.)